INTERNAL FACTORS THAT INFLUENCE TOURISTS' MOTIVATION TO TRAVEL TO PALI REGENCY, SOUTH SUMATRA (Jurnal IPTA (Industri Perjalanan Wisata), 2026)
This study investigates the factors influencing tourist motivation to visit Kabupaten PALI, South Sumatera, Indonesia. Employing a descriptive quantitative approach, the research analyzes internal (push) factors that shape domestic tourists’ travel decisions. The results indicate that push factors have a positive and statistically significant effect on tourist motivation. The determination coefficient (R² = 0.993) shows that 99.3% of the variation in tourist motivation can be explained by these internal drivers. The main push factors identified include the desire to escape daily routines, seek relaxation, strengthen family relationships, enjoy entertainment, and achieve self-fulfillment. These motivations originate from psychological and emotional needs within individuals. The findings highlight the importance of understanding tourists’ internal motivations as a basis for developing appropriate tourism strategies to increase tourist visits to Kabupaten PALI.